INFLUENCE OF INNOVATION STRATEGIES ON ORGANIZATIONAL PERFORMANCE IN ISIOLO COUNTY REFERRAL HOSPITAL, KENYA - Guyo, Boru; Thoronjo , Erastus (IJRDO - Journal of Business Management, 2022)
Innovation is one of the top priorities of management in enhancing sustainability and promoting superior performance. The innovation strategies of a given institution acquired over a given period influences significantly its performance. The purpose of the study was on the influence of innovation strategies on organizational performance in Isiolo County Referral Hospital, Kenya. The study was guided by this objective; to establish the influence of process innovation strategy on organizational performance. The theory adopted for this study was Open innovation theory. The study adapted descriptive research design. The target population was 200 employees namely; health management committee, supply chain officers, departmental supervisors, departmental heads, ICT officers and medical officers. Out of target population of 200, sample size of 80 was selected using stratified random sampling. Open and Closed ended questionnaire was used as tools for data collection. The study found out that there was a significant relationship between process innovation strategies and organizational performance. The result of chi square test established that there was a very large effect with a significance of 0.001 which makes it statistically significant This therefore implied that adoption of process of innovation influenced organizational performance. The study therefore conclude innovation strategies greatly influence organizational performance.